Gender equity in the scientific nursing journals indexed in Journal Citation Reports: A cross-sectional study - Gea-Caballero, Vicente; Ruíz de Viñaspre-Hernández, Regina; Saus-Ortega, Carlos; Celda-Belinchón, Luís; Santolalla-Arnedo, Ivan; Marques-Sule, Elena; Juárez-Vela, Raúl (Frontiers in Public Health, 2023)
Background Scientific activity has been connected to the proven inequality between women and men. To examine the state of gender equality in nursing research by analyzing the representation of male and female as editors and as authors of articles published in scientific journals. Method A cross-sectional study was carried out between September-2019 and May-2020. All the scientific publications published in 115 nursing journals indexed in the Journal Citation Reports in the years 2008, 2013, and 2017 were chosen as analysis units. The main variables studied were gender of the “journal editor”; gender of the “first author”, “last author”, “corresponding author”, and “first author in funded articles”. Descriptive and inferential analysis was performed. Results The proportion of male editors in 2008, 2013, and 2017 was 23.3, 19, and 18.5% respectively, with a male/female ratio of 1:3, 1:4 and 1:5. Male editors are mainly found in the journals of the first quartile (Q1 = 33.8%, ratio1:2), compared to the journals of the fourth quartile (Q4 = 6.6%, ratio1:14), p < 0.01. The male authorship position was “last author” (30.9%, ratio1:2), “corresponding author” (23.3%, ratio 1:3), “first author” (22.1%, ratio 1:4) and “first author in funded articles” (21.8%, ratio 1:4). Furthermore, in 19.5%, of the articles there were more male authors. The percentage of articles with male authorship increased from 2008 to 2017, “first author” (21.1–23.4%; p < 0.01), “last author” (30.0–31.1%; p = 0.22), “corresponding author” (22.5–24.2; p = 0.01), and “first author in funded articles” (18.1–25.9%; p < 0.001). Conclusions Men are over-represented in the editor role in the most prestigious nursing journals. There are a higher proportion of male authors in the main positions of authorship.